2015
DOI: 10.1016/j.jmarsys.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic response in a microtidal and shallow bay under energetic wind and seiche episodes

Abstract: In this contribution we investigate the hydrodynamic response in a micro-tidal and shallow semienclosed domain. We chose a set of observations which include currents, hydrography and meteorological data obtained in Alfacs Bay (NW Mediterranean Sea). Short-term response to energetic winds events was found in the hydrography and water velocity observations, sometimes inverting the estuarine circulation or developing one-layered flow. In comparison to previous investigations in Alfacs Bay, we observed that water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 38 publications
4
37
1
Order By: Relevance
“…The vertical profiles of temperature and salinity showed a stratified water column, with a fresher and warmer surface layer and an underlying cooler and saltier water layer (Fig 6b and 6c). The pycnocline was located at ~3.5m depth, consistent with previous studies [22, 3233]. The averaged temperature and salinity gradients between surface and bottom were of ΔT = 1.33°C and ΔS = 1.84, with maximal differences of 2.1°C and 2.7, respectively (found in the bay mouth).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The vertical profiles of temperature and salinity showed a stratified water column, with a fresher and warmer surface layer and an underlying cooler and saltier water layer (Fig 6b and 6c). The pycnocline was located at ~3.5m depth, consistent with previous studies [22, 3233]. The averaged temperature and salinity gradients between surface and bottom were of ΔT = 1.33°C and ΔS = 1.84, with maximal differences of 2.1°C and 2.7, respectively (found in the bay mouth).…”
Section: Resultssupporting
confidence: 89%
“…The strongest winds blew from SW from 5 pm to 10 pm. The observed wind pattern responded to the typical land breeze characterized by weak nocturnal winds (<2 m·s -1 ) blowing from land, that reverses the direction and increases the intensity during the daytime (sea breeze) [30, 33]. A similar behavior was observed in the surface current velocities, indicating that the water circulation at the sampling station was driven by the prevailing wind (Fig 10c).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The bay has been defined as a salt-wedge estuary (Camp and Delgado 1987) Fig.2. In general, the water column used to be stratified due to the freshwater discharge, but well-129 mixed conditions are more common during winter and mostly related to the hydrodynamic response 130 to wind forcing (Llebot et al, 2013) and occasionally to seiches (Cerralbo et al, 2015a). …”
Section: --Study Areamentioning
confidence: 99%
“…The bay has been defined as a salt-wedge estuary with an almost year-round stable stratification, alternated with well-mixed periods directly related to strong wind (Camp and Delgado, 1987) or seiche events (Cerralbo et al, 2015). Solé et al(2009) found that drainage discharges were the main factor controlling the observed stratification.…”
Section: Study Areamentioning
confidence: 99%